Pemberdayaan Kader, Ibu Hamil dan Ibu Menyusui dalam Upaya Pencegahan Stunting Pada Balita - Andi Asrina; Fairus Prihatin Idris; Nurwahdaniar Syahrul; Harismaswati Bahtiar; Dwi Islami Amir Rumae (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time as a result of providing food that is not in accordance with the nutritional needs needed. The purpose of this study is to provide understanding to partners so that they are able to understand stunting prevention. The method used is the educational method with the concept of lectures using presentation media in the form of power point appearances. Based on the results of this activity, there was an increase in knowledge and a significant change in attitude during pre-test and post-test, knowledge (p=0.000), attitude (p=0.001). Evaluation in this activity is a form of measuring the results of the pre-test and post-test questionnaires. The output obtained is an increase in knowledge and a change in attitude and the publication of mass media and publications in scientific journals.